Computer-Assisted Three-Dimensional Morphology Evaluation of Intracranial Aneurysms - Rajabzadeh-Oghaz, Hamidreza; Varble, Nicole; Shallwani, Hussain; Tutino, Vincent M.; Mowla, Ashkan; Shakir, Hakeem J.; Vakharia, Kunal; Atwal, Gursant S.; Siddiqui, Adnan H.; Davies, Jason M.; Meng, Hui (World neurosurgery, 2018)
Precise morphologic evaluation is important for intracranial aneurysm (IA) management. At present, clinicians manually measure the IA size and neck diameter on 2-dimensional (2D) digital subtraction angiographic (DSA) images and categorize the IA shape as regular or irregular on 3-dimensional (3D)-DSA images, which could result in inconsistency and bias. We investigated whether a computer-assisted 3D analytical approach could improve IA morphology assessment. Five neurointerventionists evaluated the size, neck diameter, and shape of 39 IAs using current and computer-assisted 3D approaches. In the computer-assisted 3D approach, the size, neck diameter, and undulation index (UI, a shape irregularity metric) were extracted using semiautomated reconstruction of aneurysm geometry using 3D-DSA, followed by IA neck identification and computerized geometry assessment. The size and neck diameter measured using the manual 2D approach were smaller than computer-assisted 3D measurements by 2.01 mm (P < 0.001) and 1.85 mm (P < 0.001), respectively. Applying the definitions of small IAs (<7 mm) and narrow-necked IAs (<4 mm) from the reported data, interrater variation in manual 2D measurements resulted in inconsistent classification of the size of 14 IAs and the necks of 19 IAs. Visual inspection resulted in an inconsistent shape classification for 23 IAs among the raters. Greater consistency was achieved using the computer-assisted 3D approach for size (intraclass correlation coefficient [ICC], 1.00), neck measurements (ICC, 0.96), and shape quantification (UI; ICC, 0.94). Computer-assisted 3D morphology analysis can improve accuracy and consistency in measurements compared with manual 2D measurements. It can also more reliably quantify shape irregularity using the UI. Future application of computer-assisted analysis tools could help clinicians standardize morphology evaluations, leading to more consistent IA evaluations. •Our study shows manual 2D measurements of IA size and neck diameter are smaller than the computer-assisted 3D measurements.•Manual 2D measurement and visual inspection of aneurysm shape are subject to inconsistency.•Variations in measurements and shape evaluation can influence IA morphology assessment.•Computer-assisted 3D morphology can help clinicians standardize morphology assessments.